Effect of CCl4 and Nigella sativa oil on histological changes of liver in the immature white Rats - Ata Mahdi, Dikra (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study aimed to investigat the effect of Carbon tetrachloride CCl4 and Nigella sativa oil on histological changes of liver. It was used only (20) immature male rats. to study the effect of Carbon tetrachloride CCl4 and Nigella sativa oil on changes. The rats were randomly divided into equal groups as follows. First group was injected intra dermally with 0.1 ml, normal saline (two times per weeks). This group was considered as control group .The second group was injected intra dermally with (Carbon tetrachloride CCl4 ml / 100g ) of body weight for ( two times per weeks was injected for (8weeks) . The third group It was orally given 0.1 ml dose of Nigella sativa oil, it was injected for (8weeks).The fourth group was treated with Carbon tetrachloride CCl4 and Nigella sativa oil in the same previous way. There was clear effect for Carbon tetrachloride CCl4 on liver, it was caused infiltrative cells presented by lymphocytes and phagocyte, liver cells defect; like edema, necrosis and haemolysis in liver cells, it was found catalytic effect in treated group with Carbon tetrachloride CCl4 and Nigella sativa oil liver, It appeared in normal appearance and like the control group. It showed catalytic effect in treated groups with Carbon tetrachloride CCl4 and Nigella sativa oil , and little negative in the liver.